Increasing Antibiotic Resistance in the Uropathogens (Asian Journal of Pharmaceutics (AJP), 2019)
Objective: The main objective of our study was to determine the increasing resistance in the treatment of uropathogens among urinary tract infective patients of health center of Guru Nanak Dev University, Amritsar. Materials and Methods: The study was conducted in Guru Nanak Dev University by taking the samples from the suspected patients of urinary tract infection. Culturing and identification of the uropathogens were done by the standard procedures according to Clinical and Laboratory Standards Institute guidelines. Antimicrobial susceptibility test was done to check the antibiotic resistance against uropathogens in the treatment by standard guidelines. Results: Of 102 samples, 64 were found to be positive for the uropathogens. Escherichia coli was the most prominent uropathogen and fungi such as Candida. The predominant antibiotics used were belonging to the class of aminoglycosides, cephalosporins, fluoroquinolones, nitrofurans, and penicillin. Conclusion: The study indicates that most of the uropathogens isolated from the urinary tract infective patients were resistant to the major antibiotics which were used for the treatment. This resistance was due to the improper intake of the antibiotics and poor compliance of the patient. Hence, due to the resistance, it is very hard to treat the infected patient. For proper treatment, people should be aware of the antibiotic resistance and have to change their lifestyle to remove the cause of the antibiotic resistance.